Building Character Based On The Qur'an Facing Disruption Culture Of Community In Industrial Revolution 4.0 - Jannah, Miftahol (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2025)
This paper discusses the importance of strengthening the character of student in the face of the current disruption of culture society in the industrial revolution era 4.0. This industrial era reats on intellectual engineering and the internet of thingsthan oper up unlimited space and opportunities for humans to access information and virtually and easily and at very low costs. Therefore, the 4.0 industrial revolution is predictcted as a new civilization that will present opportunities and challenges for human life. The disruption society that is raised does not only concern economic and technological aspects but also political, social, cultural and even religious education aspects. Character education based on the Qur’an as one solution to prepare and fortify humans, especially the young generation (millennial) in interacting and communicating through digitizing the virtual world by sticking tho the noble values that come from the Qur’an and sunnah Rasulullah Muahammad SAW.